Direito internacional da mulher: o reconhecimento do direito à igualdade como medida combativa à violência de gênero no sistema interamericano de Direitos humanos e sua influência no Direito processual brasileiro - Barbosa, João Paulo de Carvalho (2024)
One of the profound transformations that International Human Rights Law has undergone corresponds to the human rights of women, recognizing gender inequality as a factor of discrimination and a condition of vulnerability. The research investigates the recognition of women's human rights, through the application of the right to equality within the scope of the Inter-American Human Rights System. Based on a bibliographical and documentary methodological basis, through the observation and analysis of documents such as the Maria da Penha Law and International Human Rights Treaties and Conventions. The first part presents the internationalization of women's human rights in the Latin American scenario, dealing with the Organization of American States, the Convention on the Elimination of All Forms of Discrimination against Women and the Convention of Belém do Pará. Subsequently, the theme of the Inter-American Human Rights System as a fight against gender violence, dealing with the origin, profile and objectives of the, as well as the actions of the Inter-American Commission on Human Rights and the Inter-American Court of Human Rights in protecting human rights. woman humans. The third and last part analyzes the fight against domestic and family violence against women in Brazil, affirmative actions in the fight against discrimination, the democratic consolidation of the feminist agenda in the Federal Constitution of 1988 and, then, the analysis of the Maria da Silva case. Penha and the influence of the SIDH for the creation of Law n° 11.340/2006 as a national framework for combating domestic and family violence against women. Finally, the challenges of the IAHRS are examined for the effective guarantee that women can live with dignity, free from gender-based discriminatory violence in the Americas.